Production of glazed ceramics in south-eastern Crimea. Historical background and archaeological context - Iryna Teslenko; Oleksandr Dzhanov (Cercetări Arheologice)
During the second half of the 13th and throughout the 14th centuries, Crimea was at the epicenter of multi-ethnic and multi-cultural interactions between East and West that contributed to its economic recovery. The production of glazed ceramics became one of the new and intensively developing industries in Crimea and was one of the markers of its economic growth. It is commonly believed that it was local glazed pottery that flooded the markets of Eastern Europe and the Black Sea region for almost two centuries from the late 13th century until the Ottoman conquest of the Black Sea region in the last quarter of the 15th century. These ceramics have usually been joined in the ‘South-Eastern Crimea’ or SEK group, which, as generally considered, combined the products of the big pottery centers in Solkhat, Sougdaia, Caffa, and their vicinity. However, the attempts to identify subgroups associated with each of them are still hypothetical, largely because they are not based on material from the workshops themselves. So, we focused on the study of local glazed pottery manufacturing in Southeastern Crimea by analyzing the historical background of the emergence and development of this industry and by supplementing, clarifying, and detailing the topography, the pottery repertoires, and the chronology for each of the pottery workshops through archaeological materials.